63.4k views
2 votes
Please help I don't know lots of algebra so an explanation would also be nice :)

Please help I don't know lots of algebra so an explanation would also be nice :)-example-1
User Dlamotte
by
5.1k points

2 Answers

6 votes

Answer:


57-12x

Explanation:

In the first part you would distribute the negative


-(-9-6x) \\-(-9) = --9 = +9 = 9\\-(-6x) = --6x = +6x = 6x

So right now you have


9+6x+6(8-3x)

Now you distribute the 6


6(8) = 6 * 8 = 48\\6(-3x) = 6*-3x = 6* -3 * x = -18x

Your equation now looks like


9+6x+48-18x

Combine like terms


6x-18x = -12x\\9+48 = 57

Your answer is


57-12x aka
-12x + 57

User Banker Mittal
by
5.0k points
3 votes
PEMDAS

Parentheses
Exponents
Multiply
Divide
Add
subtract
User Dale Marshall
by
5.2k points